Catalpol-Induced AMPK Activation Alleviates Cisplatin-Induced Nephrotoxicity through the Mitochondrial-Dependent Pathway without Compromising Its Anticancer Properties. (16th January 2021) - Zhang, Jiangnan; Zhao, Tingting; Wang, Changyuan; Meng, Qiang; Huo, Xiaokui; Wang, Chong; Sun, Pengyuan; Sun, Huijun; Ma, Xiaodong; Wu, Jingjing; Liu, Kexin
Abstract : Nephrotoxicity is a common complication of cisplatin chemotherapy and, thus, limits the clinical application of cisplatin. In this work, the effects of catalpol (CAT), a bioactive ingredient extracted from Rehmannia glutinosa, on cisplatin-induced nephrotoxicity and antitumor efficacy were comprehensively investigated. Specifically, the protective effect of CAT on cisplatin-induced injury was explored in mice and HK-2 cells. In vivo, CAT administration strikingly suppressed cisplatin-induced renal dysfunction, morphology damage, apoptosis, and inflammation. In vitro, CAT induced activation of adenosine 5 ′ -monophosphate- (AMP-) activated protein kinase (AMPK), improved mitochondrial function, and decreased generation of cellular reactive oxygen species (ROS), leading to a reduction in inflammation and apoptosis, which ultimately protected from cisplatin-induced injury. However, the beneficial effects of CAT were mostly blocked by coincubation with compound C. Furthermore, molecular docking results indicated that CAT had a higher affinity for AMPK than other AMPK activators such as danthron, phenformin, and metformin. Importantly, CAT possessed the ability to reverse drug resistance without compromising the antitumor properties of cisplatin. These findings suggest that CAT exerts positive effects against cisplatin-induced renal injury through reversing drug resistance via the mitochondrial-dependent pathway without affecting the anticancer activity of cisplatin.